Your Ad Here : The Cool Sell of Guerrilla Marketing - Serazio, Michael (Book collections on Project MUSE., 2013)
"Amidst the profound upheavals in technology, economics, and culture that mark the contemporary moment, marketing strategies have multiplied, as brand messages creep ever deeper into our private lives. In Your Ad Here, an engaging and timely new book, Michael Serazio investigates the rise of "guerrilla marketing" as a way of understanding increasingly covert and interactive flows of commercial persuasion. Digging through a decade of trade press coverage and interviewing dozens of agency CEOs, brand managers, and creative directors, Serazio illuminates a diverse and fascinating set of campaign examples: from the America's Army video game to Pabst Blue Ribbon's "hipster hijack," from buzz agent bloggers and tweeters to The Dark Knight's "Why So Serious?" social labyrinth. Blending rigorous analysis with eye-opening reporting and lively prose, Your Ad Here reveals the changing ways that commercial culture is produced today. Serazio goes behind-the-scenes with symbolic creators to appreciate the professional logic informing their work, while giving readers a glimpse into this new breed of "hidden persuaders" optimized for 21st-century media content, social patterns, and digital platforms. Ultimately, this new form of marketing adds up to a subtle, sophisticated orchestration of consumer conduct and heralds a world of advertising that pretends to have nothing to sell."--Publisher's website.